(untitled) (Research, Society and Development, 2021)
The theoretical study of the applications of Biomimetics in the construction and development of solutions brings together methods, concepts and examples of applications that can awaken creativity and, at the same time, critical thinking about the recovery of the balance between human action and nature. The inspiration of Biomimetics can raise awareness about the need to adopt new technologies, standards, and survival criteria, considering the environmental balance. In this sense, the objective of this study is to describe the use of Biomimetics as a promising agent for sustainable ideas to the problems identified in ambience in animal production. With a systematic analysis of the literature, proposals for solutions already used/designed to solve existing problems are presented, through analogies with natural systems. In this way, less widespread technologies or research are pointed out, such as fast and portable constructions, structures that favor the improvement of thermal and acoustic comfort, water and sewage treatment, and renewable energy consumption. All these technologies are promising in the process of optimizing structures for animal production.